How Microanalysis Can Be Discriminant on Black Pompeian Wares - Laura Medeghini; Silvano Mignardi; Giorgia Di Fusco; Michela Botticelli; Fulvio Coletti; Caterina De Vito (Crystals, 2020)
In the present work the advantages of punctual approaches are discussed in the discrimination of black wares from the Sanctuary of Venus Fisica (Pompeii, Italy), dated between the 2nd and 1st century BC. Black-gloss ware and "bucchero" samples are analyzed by a multi-analytical approach including optical microscopy (OM), X-ray powder diffraction (XRPD), scanning electron microscopy with Energy Dispersive Spectroscopy (SEM-EDS) and electron microprobe analysis (EMPA) to investigate the mineralogical and petrographic features of these artefacts. Grain size, firing conditions and potter’s expertise influenced the final appearance of the superficial decorative black layer. In addition, punctual chemical analysis was fundamental to verify the archaeological indication of specific production sites.